Congenital arhinia: A rare case - Goyal Abhishek; Agrawal Vikesh; Raina V; Sharma D (Wolters Kluwer Medknow Publications, 2008)
Congenital arhinia or absence of nose is a rare condition with only 30 cases reported so far. We report a rare case and briefly review the literature.